THE VERBAL AND VISUAL SIGNS OF TOURIST ATTRACTION FOUND IN BALI BEST ADVENTURE MAGAZINE - I Gede Erdi Kurnia Prasetya; Ni Made Diana Erfiani; Ni Luh Desy Suari (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTThe sign can be found in many aspects of our daily life and in everywhere, for example in theadvertisement. Advertisement is a social communication which is used by the advertiserto campaign the products or services to the customer. The purpose of this study is to analyzethe verbal and visual signs and the types of meaning and function of language found in Bali BestAdventure Magazine. The data were collected by documentation, purposive sampling andinterview with Creative Designer and Director of Sales to gain more data found in theadvertisement from Bali Safari and Marine Park. The data was analyzed descriptive qualitativebased on the theory of Saussure (1966) and Leech (1981). The result of this study showed theverbal signs in the advertisement is classified into four parts such as the headline, body copy,signature line, and standing detail. Besides, the visual signs are usually described based on theillustration component in the advertisement. There were three types of meaning and functionsare identified in this study. Those meanings are conceptual, connotative and affective meaning.While the functions of language are informational, directive and expressive functions.Keywords: Verbal sign, visual sign, advertisements, types of meaning andlanguage functionsABSTRAKSebuah tanda bisa ditemukan dalam berbagai aspek kehidupan sehari-hari misalnyapada iklan. Iklan adalah komunikasi sosial yang digunakan oleh pengiklan untukmempromosikan sebuah produk atau jasa terhadap pelanggan. Tujuan dari penelitianini adalah untuk menganalisis tanda verbal dan visual serta tipe makna dan fungsibahasa yang terdapat dalam majalah Bali Best Adventure. Data ini dikumpulkandengan menggunakan metode dokumentasi, sampling purposive dan wawancaradengan pembuat iklan dan Direktur Penjualan untuk memperoleh banyak data yangditemukan pada iklan Bali Safari and Marine Park. Penelitian ini menggunakandeskriptif kualitatif berdasarkan pada teori Saussure (1966) dan Leech (1981). Hasilpenelitian ini menunjukkan tanda verbal pada iklan dikelompokkan menjadi empatbagian yaitu judul iklan, konten iklan, brand atau harga dari suatu produk dan caramemperoleh suatu informasi terhadap iklan tersebut. Di samping itu, tanda visualdideskripsikan berdasarkan pada sebuah komponen illustrasi yang terdapat pada iklan.Ada tiga jenis makna dan fungsi bahasa yang diidentifikasi pada penelitian ini. Tipemakna tersebut adalah makna konseptual, konotatif dan afektif. Sedangkan pada fungsibahasa yaitu fungsi informasional, direktif dan expresif.Kata kunci: Tanda verbal, tanda visual, iklan, tipe makna dan fungsi bahasa.